Knowledge, attitudes, and practice of leadership skills among undergraduate medical students: Leadership in Medical Education - Hjiej, Ghita; Touissi, Youness; Chouhab, Omar; Hssein, Jihane; Bentata, Yassamine; Hajjioui, Abderrazak; Fourtassi, Maryam (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Medical knowledge alone is insufficient to provide excellent medical care. Modern healthcare challenges require that all physicians have leadership skills in order to better cooperate and collaborate with other healthcare professionals and effectively lead their teams to provide the best possible care to their patients. The objective of this study was to describe medical students’ prior knowledge of leadership concepts, to assess their common practice of its main skills and to explore their general perception of its application by their seniors.Methods: Non-graduated medical students enrolled in the 5th year of medicine or above were invited to fill-in an anonymous online questionnaire. 267 students (66% women) from different medical faculties took part in the study.Results: 44% of the participants had a vague idea about leadership and 29% were completely ignorant of the concept. 52% of them thought that leadership was not to be expected from medical students, and 65% did not know that leadership in healthcare would benefit the patient. In their responses to simulated situations, the participants presented optimal attitudes embracing leadership attributes regarding self-awareness, receiving feedback, teamwork, stress and conflict management, however they present more contrasting attitudes when it came to time management and questioning oneself. Seniors with good leadership skills were perceived as few by half the participants.Conclusions: This survey highlighted the need of introducing specific leadership training programs within the curriculum of medical studies in Morocco.